The β-Glucoside (bgl) Operon of Escherichia coli Is Involved in the Regulation of oppA, Encoding an Oligopeptide Transporter - Harwani, Dharmesh (American Society for Microbiology, 2012)
We report that the bgl operon of Escherichia coli, encoding the functions necessary for the uptake and metabolism of aryl-β-glucosides, is involved in the regulation of oligopeptide transport during stationary phase. Global analysis of intracellular proteins from Bgl-positive (Bgl(+)) and Bgl-negative (Bgl(−)) strains revealed that the operon exerts regulation on at least 12 downstream target genes. Of these, oppA, which encodes an oligopeptide transporter, was confirmed to be upregulated in the Bgl(+) strain. Loss of oppA function results in a partial loss of the growth advantage in stationary-phase (GASP) phenotype of Bgl(+) cells. The regulatory effect of the bgl operon on oppA expression is indirect and is mediated via gcvA, the activator of the glycine cleavage system, and gcvB, which regulates oppA at the posttranscriptional level. We show that BglG destabilizes the gcvA mRNA in vivo, leading to reduced expression of gcvA in the stationary phase. Deletion of gcvA results in the downregulation of gcvB and upregulation of oppA and can partially rescue the loss of the GASP phenotype seen in ΔbglG strains. A possible mechanism by which oppA confers a competitive advantage to Bgl(+) cells relative to Bgl(−) cells is discussed.